Penerapan Pemberian Aromaterapi Lavender Terhadap Intensitas Nyeri Post Sectio Caesarea Pada Ny. R Di Rumah Sakit Islam Malahayati Medan - Bela Juliana Harahap; Afiatika Ahsani (STIKES Columbia Asia Medan, 2025)
cesarean section is a delivery technique that involves making an incision in the uterine wall (hysterotomy) through the front abdominal wall (laparotomy). The action of a cesarean section causes a change in the continuity of body tissues that results in pain. This writing aims to apply the provision of lavender aromatherapy as a non-pharmacological nursing intervention at the Islamic Hospital Malahayati Medan, 2nd Floor New Room. This type of writing is a case study using a nursing care approach for a 35-year-old mother diagnosed with post-cesarean section. The intervention provided was the administration of lavender aromatherapy using inhalation methods with a diffuser, by adding 1 cc of lavender essential oil and 10 cc of clean water into the humidifier for 10 – 15 minutes over 3 consecutive days. This was indicated by the patient reporting that pain decreased to a pain scale of 3 from a pain scale of 6. Lavender aromatherapy therapy has proven to be effective as a non-pharmacological therapy in reducing pain intensity after Caesarean section